Optimization of a Non-Invasive Solar Desalination Prototype Using a Hybrid Desalination System (PV-TE) for Off-Grid Clean Water Production in the Region - Roy Lamrun Sianturi; Rinaldo Hasudungan Malau; Tiara Melinda (Gio Vani Publisher, 2026)
Access to clean water in Indonesia's remote coastal areas requires a self-sufficient and sustainable desalination solution. This study aims to optimize a prototype of a non-invasive solar desalination system by integrating Photovoltaic-Thermoelectric (PV-TE) hybrid technology for off-grid clean water production. A pilot-scale unit was developed from a basic passive solar distillation prototype through the addition of photovoltaic panels and thermoelectric modules that double as waste heat recoverers and active condenser coolers. Test results show significant performance improvements, with conductivity removal efficiency reaching 99.83% with ultra-pure water quality (80 µS/cm). Water productivity increased exponentially by 1148%, from 0.50 L/day.m² in the basic prototype to 6.24 L/day.m² in the hybrid system, with a system energy conversion efficiency reaching 29.05%. These findings confirm that the strategic integration of PV-TE components not only overcomes productivity limitations in passive solar desalination but also offers an autonomous desalination solution with low environmental impact. This research contributes to the development of self-sufficient water infrastructure that can be replicated in coastal communities with abundant solar intensity.